FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN BASIC INDUSTRY DI BEI - Wardoyo, Teguh (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to test and analyze whether capital structure, sales growth, company size have an effect on company value. Then the next objective is to test and analyze whether dividend policy is able to moderate capital structure, sales growth and company size on company value.This research is a type of explanatory research.The population of this research is public